Effects of Umami Taste on Visual Food Cue Processing: An ERP Study with Source Localization - Anne Schienle; Florian Osmani; Emilia Iannilli (Foods)
Research suggests that monosodium glutamate (MSG), known for its association with umami taste, may influence appetite. This event-related potential (ERP) study with source localization examined the effects of umami taste on visual food cue reactivity. A total of 88 females (mean age: 26 years) were randomly assigned to one of two groups: one tasted an MSG solution, while the other tasted water, before viewing images from four food categories with varying umami concentrations (meat dishes, vegetables, fruits, sweets). The participants rated their desire to eat the depicted foods, and ERP late positivity (P300; late positive potential: LPP) was analyzed. The results showed that MSG did not influence reported appetite. However, the MSG group exhibited reduced parietal P300/LPP amplitudes across all food categories. These group differences in food cue processing could be traced back to sources in the left occipital gyrus and fusiform gyrus indicating an alteration in motivated attention due to umami taste.